Sustainable Tourism: An issue of Territorial Rebalancing in the French département of Pyrénées-Orientales - Berthet, Nicolas (Téoros)

(untitled) (Université du Québec à Montréal, 2012)
Bordered by Spain to the south, between the Mediterranean Sea and the Pyrenees mountains, the French département of Pyrénées-Orientales, also known as Northern Catalonia or French Catalonia, has long seemed to be an outlying rural area, isolated, with very little industry. The advent in the 1960s of the Mission Interministérielle d’Aménagement touristique du littoral du Languedoc-Roussillon (also known as the Racine Mission, after its director, Pierre Racine), would quickly turn the département into a major southern France tourist destination. The dynamic of developing the coastal plain contrasted with the decline of agriculture and the rural exodus taking place in the backcountry. Aware that a preserved rural and natural setting nonetheless had tourism potential, various neo-rural populations moved to the backcountry starting in the 1970s. They developed nature tourism in this area at the beginning of the 1980s. Although it was marginal compared to the activity generated by mass tourism on the coast and at ski resorts, backcountry nature tourism was the starting point for future sustainable tourism development in the Pyrénées-Orientales.By referring to stakeholder networking initiatives, as well as public transportation policies, this article offers a description of the innovative processes set up and/or maintained by the Conseil Général des Pyrénées-Orientales in the area of sustainable tourism. The outcome of discussions in a professional capacity with various actors in local tourism, this article stresses the importance of the engagement of local authorities, in this case the Conseil Général des Pyrénées-Orientales, to carry through with sustainable development of tourism in a Mediterranean destination that is still largely given over to mass tourism.